GENESIS DAN KARAKTERISASI GEOKIMIA DI LAPANGAN SUBAN, CEKUNGAN SUMATERA SELATAN - KUSUMA UTAMA , MOHAMMAD
There has been a strength of growth of gas reserves in Indonesia which will cause a continued shift from oil to gas production as mature oil fields are depleted. Exploration efforts during the last ten years have been awarded by discoveries of significant and large to giant gas fields distributed all over Indonesia. Therefore, a knowledge of the origin, distribution, and habitat of natural gases are important for focusing gas exploration. Regional knowledge of gas geochemistry will result in more efficient gas exploration strategy. Rock samples analyzed in the well SBU-1 shows that the total organic carbon content (TOC) ranges from low to sufficient potential. Telisa Formation has TOC values ranging between 0.75 and 1.22%, Formation (equivalent) Baturaja between 0.44 and 1.36% while Talangakar Formation ranges from 1.23 and 1.66%. The results of the Rock-Eval data plot on the modification van Krevelen diagram shows that the majority of the analyzed rock sample is Type III kerogen (gas prone). Interpretation of maturity indicates that the level of early maturity occurs at a depth of 2600 m and begin to produce hydrocarbons below this depth. Analysis of gas composition in detail has been carried out on 7 (seven) gas samples taken from wells Durian Mabok-2, Suban-3, Suban-4, Suban-5, Suban-6, Suban-7, Suban-9, SBB-1 , SBB-2 and SBU-1. The composition of these gases are generally similar and dominated by the hydrocarbon components with a value of between 84.56% mole and 98.13% mole. Gas methane (CH4) is the most abundant component with values between 75.98% mole and 89.83% mole while the content of the wet gas (C2-C5) is quite high (5.88 to 22.57%), indicating that the pure gases are thermogenic on the first possibility. Cross-plot method of methane ?13CCH4 geochemistry of hydrocarbon formation indicates that gas in the Field Suban divided into two types of gas and vi thermogenic gas is biogenic gas. This was confirmed by the results of cross-plot ?13CCH4 against the concentration of C2+ which shows that in the research area there are two different types of gas origin. The composition of stable carbon isotopes of CO2 components found in the research area indicates that the value varies between -0.28% and -14.15%. The results of the cross-plot shows that the CO2 comes from two sources include mantle activity or volcanic and biogenetic sources.